Experimental Study of Visible Light Communication Links with a Strong Line of Sight Component - Soto-Gomez, J (Institute of Electrical and Electronics Engineers Inc., 2023)
The importance of studying visible light communications (VLC) systems is present today and growing each day due to the possibilities of higher data rates, security, and various applications. In this manuscript, we study the behavior of the channel frequency response (CFR) considering different configurations of parameters and distances in an experimental setup. We also study the noise distribution seen at the receiver by computing a first-order estimator of the received signal. The results show that it is necessary to account for the internal circuitry of the equipment used to determine an optimum range of operating frequencies because VLC links seem to be frequency selective. © 2023 IEEE.